Two-dimensional mesoporous oxide'cluster alkene 'catalyst and preparation method thereof
Through a new preparation method, low-order phenolic resin and structural guide agent are used to co-assemble with metal salt precursors to form a two-dimensional mesoporous oxide "cluster-like olefin" catalyst, solving the problems of cumbersome synthesis and reduced activity in the prior art, and achieving a catalyst with high activity, high stability and simple synthesis steps, suitable for industrial applications.
Patent Information
- Application Number
- CN202411240720.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-04-25
AI Technical Summary
The existing two-dimensional mesoporous oxide "cluster-like olefin" catalytic materials have complicated synthesis methods, and the organic ligands of cluster assembly units are difficult to eliminate or have poor thermal stability, resulting in a decrease in catalyst activity and is difficult to widely use in industry.
By preparing a low-order phenolic resin, a structural guide agent and a metal salt precursor, a lyophilized liquid crystal phase precursor solution is formed, and then assembled through a single micelle interface on a soluble sodium chloride crystal substrate, and a two-dimensional mesoporous oxide "cluster-like olefin" catalyst is further formed by in-situ thermal reduction and directional growth.
The catalyst is achieved with high activity and high stability, the synthesis steps are simple, and it is suitable for the preparation of various oxides "cluster-like olefins". It shows excellent catalytic performance in the directional oxidation reaction of 5-hydroxymethylfurfural, achieving a conversion rate of 100% and a selectivity of ≥99%.
Smart Images

Figure CN119869501A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic synthesis, and in particular to a two-dimensional mesoporous oxide "cluster olefin-like" catalyst and a preparation method thereof. Background Art
[0002] Metal / metal oxide clusters have high atomic utilization efficiency, high exposure rate and high accessibility due to their atomically precise structure, high specific surface area and low coordination number, and thus are of vital importance in basic research and industrial applications. In recent years, researchers have also found that the interaction between cluster units can greatly affect the overall structure and properties of clusters. When nanoclusters are directly connected together instead of being separated by ligands, unique structures and unexpected properties may appear. For example, when cluster units are co-assembled into a two-dimensional "cluster-like ene", the clusters are directly connected to each other, and their solution behavior and electronic structure will be greatly affected by their ultra-high surface atomic ratio, showing unique electron delocalization characteristics. In addition, two-dimensional mesoporous materials have atomic-scale thickness, high exposed surface atoms, dangling bonds, surface defects, etc., providing a large and special surface area and showing special physical, chemical and electronic properties. Therefore, assembling two-dimensional mesoporous materials with cluster structures to form a "cluster-like ene" structure is expected to simultaneously couple the unique advantages of two-dimensional mesoporous structures and clusters, optimize the transport and diffusion of substances, strengthen the electron delocalization characteristics, and greatly improve their catalytic and chemical reaction activity.
[0003] At present, common synthesis methods of two-dimensional mesoporous oxide "cluster olefin" catalytic materials include room temperature wet chemical synthesis, cluster-nucleus co-assembly, cluster-block copolymer inorganic salt interface assembly, etc. (Nature Synthesis, 2023, 2, 989; Nature Chemistry, 2022, 14, 433; Advanced Materials, 2020, 32, 1906653). However, the technical bottlenecks faced by the existing synthesis methods of two-dimensional mesoporous oxide "cluster olefin" catalytic materials are: (1) the cluster assembly unit needs to be pre-synthesized first, and the preparation process is relatively cumbersome; (2) the organic ligands of the pre-synthesized cluster assembly unit are difficult to eliminate or have poor thermal stability; (3) the assembly process relies on the assistance of organic ligands, resulting in a decrease in cluster activity. So far, there is no relevant report on the preparation of two-dimensional mesoporous oxide "cluster olefin" catalysts under in situ one-step conditions. Therefore, it is still very challenging to develop a universal preparation method for two-dimensional mesoporous oxide "cluster olefin" catalytic materials with both high stability and high activity. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is that the existing method for synthesizing a catalyst with a cluster structure, the obtained clusters cannot form a highly continuous and ordered structure, the preparation process is relatively cumbersome and difficult to control, and the organic ligands of the pre-synthesized cluster assembly units are difficult to eliminate or have poor thermal stability, making it difficult to be widely used in industry. A two-dimensional mesoporous oxide "cluster olefin" catalyst and a preparation method thereof of the present invention, the catalyst has ultra-high atomic density oxygen vacancies, is an oxidation catalyst with excellent performance, the preparation method has simple synthesis steps, is suitable for the preparation of various oxide "cluster olefins", and has high catalyst activity and good stability.
[0005] To achieve the above-mentioned purpose, the present invention provides a method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst, comprising first preparing a low-order phenolic resin, then co-assembling the low-order phenolic resin, a structure directing agent and a metal salt precursor to form a lyotropic liquid crystal phase precursor solution, and then forming a two-dimensional ordered mesophase on a soluble sodium chloride crystal substrate through single micelle interface assembly, further forming a two-dimensional mesoporous oxide "cluster olefin"@sodium chloride complex through in situ thermal reduction and directional growth, and finally removing the sodium chloride crystal substrate through distilled water washing to obtain the final two-dimensional mesoporous oxide "cluster olefin" catalyst.
[0006] Further, the low-order phenolic resin is prepared, specifically comprising selecting a carbon source and an auxiliary agent and uniformly dispersing them in an organic solution; fully stirring at 50-100° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and adjusting the pH value to obtain the low-order phenolic resin.
[0007] Furthermore, the method specifically includes placing a low-order phenolic resin in a mixed solution of a structure directing agent and a metal source, and co-assembling to form a lyotropic liquid crystal phase precursor solution through a sol-gel process. During the mixing process, the metal source forms a weak coordination with the low-order phenolic resin, thereby being uniformly dispersed on the surface of the phenolic resin, and forming a two-dimensional mesoporous oxide "cluster olefin"@sodium chloride complex through in-situ thermal reduction and directional growth. Finally, the sodium chloride crystal substrate is removed by washing with distilled water to obtain the final two-dimensional mesoporous oxide "cluster olefin" catalyst.
[0008] Furthermore, the carbon source includes one or more of phenol, resorcinol, catechol, hydroquinone and formaldehyde; and the mass content of the carbon source is 5-30%.
[0009] Furthermore, the auxiliary agent includes one or more of melamine, urea, 3-mercaptopropyltrimethoxysilane and triphenyl phosphite.
[0010] Furthermore, the organic solvent includes one or more of methanol, ethanol and isopropanol; the pH value is 6-8; the amphiphilic block copolymer is a triblock copolymer F127 (EO 106 PO 70 EO106 ) and P123(EO 20 PO 70 EO 20 ) one or two; the reaction temperature is 40°C, and the reaction time is 0.5-4 hours.
[0011] Furthermore, the metal source includes one of titanium tetrachloride, niobium pentachloride, molybdenum chloride, ammonium molybdate, and cerium chloride / cerium nitrate.
[0012] Furthermore, the two high-temperature calcination stages include a first high-temperature calcination stage and a second high-temperature calcination stage, wherein the first high-temperature calcination stage is to remove the block copolymer under an inert atmosphere to obtain a metal oxide "cluster olefin"-carbon polymer @ sodium chloride complex, and the second high-temperature calcination stage is to obtain a metal oxide "cluster olefin"-carbon @ sodium chloride complex by high-temperature calcination carbonization under an inert atmosphere, and finally the sodium chloride crystal substrate is removed by washing with distilled water to obtain the final two-dimensional mesoporous oxide "cluster olefin" catalyst.
[0013] Furthermore, the temperature of the thermal polymerization process is 80-120°C, and the thermal polymerization time is 12-72 hours; the calcination temperature of the first high-temperature calcination stage is 200-400°C, and the calcination time is 3-8 hours; the calcination temperature of the second high-temperature calcination stage is 500-900°C, and the calcination time is 3-5 hours, and the inert atmosphere is nitrogen or argon.
[0014] In a preferred embodiment of the present invention, a two-dimensional mesoporous oxide cluster olefin catalyst is provided, which is obtained by the above-mentioned preparation method.
[0015] In another preferred embodiment of the present invention, a two-dimensional mesoporous oxide cluster olefin catalyst is used in the directed oxidation reaction of 5-hydroxymethylfurfural.
[0016] Technical Effects
[0017] The preparation method of the catalyst of the present invention has simple synthesis steps, is suitable for the preparation of various oxide cluster alkenes, has high catalyst activity and good stability, exhibits excellent catalytic performance in the directional oxidation reaction of 5-hydroxymethylfurfural, and achieves 100% conversion rate of 5-hydroxymethylfurfural and ≥99% selectivity of 2,5-furandicarboxaldehyde under room temperature and alkali-free reaction conditions.
[0018] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The CeO of a preferred embodiment 1 of the present invention 2-x-Spherical aberration corrected high-angle annular dark field scanning transmission electron microscopy (CS-HAADF-STEM) image of C;
[0020] Figure 2 The CeO of a preferred embodiment 1 of the present invention 2-x -C high-power spherical aberration corrected high-angle annular dark field scanning transmission electron microscope (CS-HAADF-STEM);
[0021] Figure 3 The CeO of a preferred embodiment 1 of the present invention 2-x - X-ray diffraction (XRD) pattern of C;
[0022] Figure 4 The CeO of a preferred embodiment 1 of the present invention 2-x -Atomic force microscopy (AFM) image of C;
[0023] Figure 5 The CeO of a preferred embodiment 1 of the present invention 2-x -Electron paramagnetic resonance (EPR) pattern of C;
[0024] Figure 6 A preferred embodiment of the present invention is TiO 2-x - Transmission electron microscopy (TEM) image of C;
[0025] Figure 7 is a transmission electron microscope (TEM) image of Nb2O5-C of a preferred embodiment 8 of the present invention;
[0026] Figure 8 MoO is a preferred embodiment 9 of the present invention. x -Transmission electron microscopy (TEM) image of C. DETAILED DESCRIPTION
[0027] Embodiment 1:
[0028] (1) Preparation of low-order phenolic resin
[0029] 1.5 g of phenol and 28 g of formaldehyde were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (PF).
[0030] (2) Introduction and growth of oxide clusters
[0031] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.32 g of cerium chloride. Through the sol-gel process, the cerium chloride forms a weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80° C. on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200° C. for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500° C. for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, a two-dimensional ultrathin mesoporous CeO is obtained by washing with distilled water. 2-x -C "cluster olefin" catalyst. Figure 1 As shown, the CeO 2-x -C has a highly ordered two-dimensional hexagonal structure with highly uniform pore size distribution of about 15-20nm; Figure 2 As shown, CeO 2-x -C framework is composed of highly uniform CeO 2-x (1-2nm) clusters; Figure 3 As shown, the CeO 2-x This indicates that CeO2 is evenly dispersed on the carbon carrier without large particles; Figure 4 As shown, the CeO 2-x -C is a two-dimensional ultrathin nanosheet (thickness is about 8nm); Figure 5 As shown, the CeO 2-x -C has an ultra-high oxygen vacancy concentration.
[0032] Embodiment 2:
[0033] (1) Preparation of low-order phenolic resin
[0034] 0.7 g of resorcinol and 28 g of formaldehyde were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (PF).
[0035] (2) Introduction and growth of oxide clusters
[0036] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.32 g of cerium chloride. Through the sol-gel process, the cerium chloride forms a weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80° C. on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200° C. for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500° C. for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, a two-dimensional ultrathin mesoporous CeO is obtained by washing with distilled water. 2-x -C "cluster olefin" catalyst.
[0037] Embodiment 3:
[0038] (1) Preparation of low-order phenolic resin
[0039] 0.7 g of resorcinol, 28 g of formaldehyde and 0.5 g of trimethyl phosphite were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (P-PF).
[0040] (2) Introduction and growth of oxide clusters
[0041] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.32 g of cerium chloride. Through the sol-gel process, the cerium chloride forms a weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80° C. on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200° C. for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500° C. for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, a two-dimensional ultrathin mesoporous P-CeO is obtained by washing with distilled water. 2-x -C "cluster olefin" catalyst.
[0042] Embodiment 4:
[0043] (1) Preparation of low-order phenolic resin
[0044] 0.7 g of resorcinol, 28 g of formaldehyde and 0.5 g of melamine were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (N-PF).
[0045] (2) Introduction and growth of oxide clusters
[0046] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.32 g of cerium chloride. Through the sol-gel process, the cerium chloride forms a weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80° C. on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200° C. for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500° C. for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, a two-dimensional ultrathin mesoporous N-CeO is obtained by washing with distilled water. 2-x -C "cluster olefin" catalyst.
[0047] Embodiment 5:
[0048] (1) Preparation of low-order phenolic resin
[0049] 0.7 g of resorcinol, 28 g of formaldehyde and 0.5 g of 3-mercaptopropyltrimethoxysilane were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (S-PF).
[0050] (2) Introduction and growth of oxide clusters
[0051] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.32 g of cerium chloride. Through the sol-gel process, the cerium chloride forms a weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80° C. on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200° C. for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500° C. for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, the two-dimensional ultrathin mesoporous S-CeO is obtained by washing with distilled water. 2-x-C "cluster olefin" catalyst.
[0052] Embodiment 6:
[0053] (1) Preparation of low-order phenolic resin
[0054] 1.5 g of phenol and 28 g of formaldehyde were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (PF).
[0055] (2) Introduction and growth of oxide clusters
[0056] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.43 g of cerium nitrate hexahydrate. Through the sol-gel process, cerium chloride forms weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80° C. on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200° C. for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500° C. for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, a two-dimensional ultrathin mesoporous CeO is obtained by washing with distilled water. 2-x -C "cluster olefin" catalyst.
[0057] Embodiment 7:
[0058] (1) Preparation of low-order phenolic resin
[0059] 1.5 g of phenol, 28 g of formaldehyde and 0.5 g of melamine were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (PF).
[0060] (2) Introduction and growth of oxide clusters
[0061] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.45 g of titanium tetrachloride. Through the sol-gel process, cerium chloride forms weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80°C on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200°C for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500°C for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, a two-dimensional ultrathin mesoporous TiO2 is obtained by washing with distilled water. 2-x -C "cluster olefin" catalyst.
[0062] Embodiment 8:
[0063] (1) Preparation of low-order phenolic resin
[0064] 0.7 g of resorcinol, 28 g of formaldehyde and 0.5 g of melamine were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (PF).
[0065] (2) Introduction and growth of oxide clusters
[0066] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.5 g of niobium chloride. Through the sol-gel process, cerium chloride forms weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80°C on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200°C for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500°C for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, the catalyst having two-dimensional ultra-thin mesoporous Nb2O5-C "cluster olefin" is obtained by washing with distilled water.
[0067] Embodiment 9:
[0068] (1) Preparation of low-order phenolic resin
[0069] 1.5 g of phenol and 28 g of formaldehyde were uniformly dispersed in an ethanol solution of sodium hydroxide, and fully stirred at 50° C. to obtain a low molecular weight polymer of phenol and formaldehyde, and the pH was further adjusted to 7 to obtain a low-order phenolic resin polymer (PF).
[0070] (2) Introduction and growth of oxide clusters
[0071] The low-order phenolic resin in step (1) and 1.5 g of F127 structure directing agent are placed in an ethanol solution containing 0.64 g of molybdenum chloride. Through the sol-gel process, cerium chloride forms weak coordination with the phenolic resin during the mixing process to form a two-dimensional ordered mesoscopic phase. Subsequently, a mesoporous oxide "cluster olefin"-block copolymer@sodium chloride complex is formed during a thermal polymerization process at 80° C. on a sodium chloride crystal substrate. Then, two high-temperature calcination stages are performed. The first high-temperature calcination stage is performed at 200° C. for 3 hours in an inert atmosphere to remove the block copolymer to obtain a metal oxide "cluster olefin"@sodium chloride complex. The second high-temperature calcination stage is performed at 500° C. for 3 hours in an inert atmosphere to perform high-temperature calcination and carbonization to stabilize the ordered mesoporous structure. Finally, a two-dimensional ultrathin mesoporous MoO is obtained by washing with distilled water. x -C "cluster olefin" catalyst.
[0072] Example 1-5: By changing the carbon source and ligand of the phenolic resin, the molecular weight and defect sites of the phenolic resin polymer are adjusted, and finally the two-dimensional mesoporous CeO 2-x -C "cluster olefin" catalyst skeleton is highly uniform CeO 2-x (1-2nm) clusters with ultra-high atomic density oxygen vacancies; in Examples 1 and 6, different cerium sources were changed, and the catalyst finally obtained was highly uniform two-dimensional mesoporous CeO 2-x (1-2nm) cluster ene, which has ultra-high atomic density oxygen vacancies; Examples 6-9 change different metal sources to obtain two-dimensional mesoporous CeO 2-x , TiO 2-x , Nb2O5, MoO x (1-2nm) “cluster-like olefins” catalysts all have ultra-high atomic density oxygen vacancies, among which TiO 2-x , Nb2O5, MoO x (1-2nm) "Cluster ene-like" catalysts have more acidic sites, which is beneficial to accelerate the directional oxidation rate of 5-hydroxymethylfurfural.
[0073] Embodiment 10:
[0074] Preparation of CeO with different carbon sources 2-x-C "cluster olefin" catalyst was used to catalyze the directional oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxaldehyde. 10 mg of catalyst was weighed into a 10 mL two-necked flask, 5 mL of toluene was added for dispersion, and then 126 mg of raw material 5-hydroxymethylfurfural (5-HMF) was added. After adding the corresponding additives, the reaction was carried out at 110 °C. The products detected included 2,5-diformylfuran (DFF), 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), 5-formyl-2-furancarboxylic acid (FFCA) and 2,5-furandicarboxylic acid (FDCA). The results are shown in Table 1:
[0075] Table 1
[0076]
[0077]
[0078] Embodiment 11:
[0079] Preparation of CeO with different ligands 2-x -C cluster olefin catalyst was used to catalyze the selective oxidation of 5-hydroxymethylfurfural to target products. 10 mg of catalyst was weighed into a 10 mL two-necked flask, 5 mL of toluene was added for dispersion, and then 126 mg of raw material 5-hydroxymethylfurfural (5-HMF) was added. After adding the corresponding additives, the reaction was carried out at 110 °C. The results are shown in Table 2:
[0080] Table 2
[0081]
[0082] Embodiment 12:
[0083] Preparation of TiO with different metal salts 2-x -C, Nb2O5-C and MoO x -C cluster olefin catalyst was used to catalyze the selective oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxaldehyde. 10 mg of catalyst was weighed into a 10 mL two-necked flask, 5 mL of toluene was added for dispersion, and then 126 mg of raw material 5-hydroxymethylfurfural (5-HMF) was added. After adding the corresponding additives, the reaction was carried out at 110 °C. The results are shown in Table 3:
[0084] Table 3
[0085]
[0086]
[0087] Embodiment 13:
[0088] The CeO prepared in Example 1 2-x-C cluster ene catalyst was used for multiple cycles to catalyze the selective oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxaldehyde. For the first time, 10 mg of catalyst was weighed into a 10 mL two-necked flask, 5 mL of toluene was added for dispersion, and then 126 mg of raw material 5-hydroxymethylfurfural (5-HMF) was added. After the corresponding additives were added, the reaction was carried out at 110 °C. After each reaction, the catalyst was centrifuged and washed with water. The above operation was repeated for recycling. The results are shown in Table 4:
[0089] Table 4
[0090]
[0091] The two-dimensional ultrathin mesoporous cerium dioxide with ultra-high atomic density vacancies described in the present invention directly selectively oxidizes alcohol to generate aldehyde in an alkali-free system, and has the advantages of high activity, high selectivity and being green.
[0092] The catalyst of the present invention utilizes a sol-sol process to synthesize a series of oxide clusters, and the overall synthesis steps are simple, green, and efficient, and is suitable for the preparation of various oxide cluster alkenes. The catalyst of the present invention is applied to the directional oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxaldehyde, and a 100% substrate conversion rate and ≥99% 2,5-furandicarboxaldehyde reaction selectivity are obtained. The reaction process is green and efficient, the catalyst has high activity and good stability, and has good application prospects.
[0093] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst, characterized in that: The method includes preparing a phenolic resin in advance, then co-assembling it with a metal salt precursor on the surface of a structure directing agent to form a lyotropic liquid crystal phase precursor solution, then forming a two-dimensional ordered mesophase through single micelle interface assembly on a soluble crystal substrate, and further forming a two-dimensional mesoporous oxide "cluster olefin"@sodium chloride complex through in-situ thermal reduction and directional growth; finally, removing the sodium chloride crystal substrate through distilled water washing to obtain a final two-dimensional mesoporous oxide "cluster olefin" catalyst.
2. A method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst as claimed in claim 1, characterized in that: The preparation of phenolic resin specifically includes selecting carbon source and auxiliary agent and uniformly dispersing them in an organic solution of alkaline catalyst; fully stirring at 30-70°C to obtain a low molecular weight polymer of phenol and formaldehyde; and adjusting pH value to obtain a low molecular weight phenolic resin polymer.
3. The method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst according to claim 1, characterized in that: Specifically, the method includes placing a phenolic resin and a structure directing agent in a metal salt precursor solution, and through a sol-gel process, the metal source forms a weak coordination with the phenolic resin during the mixing process, thereby being uniformly dispersed in the phenolic resin-block copolymer nanocomposite skeleton, and then directionally growing into a two-dimensional ordered mesoscopic phase on a sodium chloride crystal substrate to form a two-dimensional mesoporous oxide "cluster olefin"@sodium chloride complex, and then going through two high-temperature calcination stages, and finally removing the sodium chloride crystal substrate by washing with distilled water to obtain the final two-dimensional mesoporous oxide "cluster olefin" catalyst.
4. A method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst as claimed in claim 2, characterized in that: The carbon source comprises one or more of phenol, resorcinol, catechol, hydroquinone and formaldehyde; the mass content of the carbon source is 5-30%.
5. A method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst as claimed in claim 2, characterized in that: The auxiliary agent includes one or more of melamine, urea, 3-mercaptopropyltrimethoxysilane and triphenyl phosphite.
6. A method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst as claimed in claim 2, characterized in that: The alkaline catalyst comprises one or two of sodium hydroxide and ammonia water, and the mass content of the alkaline catalyst is 0.1-10%.
7. A method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst as claimed in claim 3, characterized in that: The metal source includes one of titanium tetrachloride, niobium pentachloride, molybdenum chloride, ammonium molybdate, and cerium chloride / cerium nitrate.
8. The method for preparing a two-dimensional mesoporous oxide "cluster olefin" catalyst according to claim 3, characterized in that: The two high-temperature calcination stages include a first high-temperature calcination stage and a second high-temperature calcination stage, wherein the first high-temperature calcination stage is to remove the structure directing agent under an inert atmosphere to obtain a metal oxide "cluster olefin"-carbon polymer @ sodium chloride complex, and the second high-temperature calcination stage is to carbonize the metal oxide "cluster olefin"-carbon @ sodium chloride complex by high-temperature calcination under an inert atmosphere.
9. A two-dimensional mesoporous oxide "cluster olefin" catalyst, characterized in that: The method is obtained by any one of claims 1 to 8.
10. Use of the two-dimensional mesoporous oxide "cluster olefin" catalyst as claimed in claim 9 in the directed oxidation reaction of 5-hydroxymethylfurfural.